TUMOR MIMIC: A RARE CASE OF PITUITARY ADENOMA MANIFESTING AS CENTRAL DIABETES INSIPIDUS - Tabora, Joebeth; Siy , Patrick (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE Central diabetes insipidus is a common complication following transsphenoidal surgery for pituitary adenomas, but CDI as an initial presentation in pituitary adenomas is extremely rare. We report a 67-year-old Filipino male with pituitary macroadenoma presenting as central diabetes insipidus, manifesting with a two-month history of severe frontotemporal headache, increased thirst, and polyuria managed with desmopressin followed by transsphenoidal surgery. Three months postoperatively, the thyroid and adrenocorticotropic axis remained intact, and pituitary bright spot recovery was observed. He was clinically stable; hence desmopressin was gradually tapered anddiscontinued. Treatment options for preoperative CDI may include surgical or medical management, with some cases reported as self-limiting. More clinical studies are needed to understand the course of this condition entirely. This case highlights a unique presentation of central diabetes insipidus in a pituitary macroadenoma and the possibility of complete resolution of symptoms post-transsphenoidal surgery.